(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Concentrations of heavy metals such as As, Cd, Co, Cr, Ni, Fe, Zn, Pb, Hg and Cu in surface water and soils were determined by using Atomic Absorption Spectrophotometer (AAS) using standard analytical methods. The physicochemical and anionic properties of the surface water were also determined to assess the pollution level of this area. The results reveal that although few parameters of the surface water are within the standard value but most of the physicochemical and anionic parameters such as BOD, COD, F-, NO3-, NH3 and Pb of the surface water are significantly higher than the standard for drinking water. The result suggests that the surface water of this area is polluted by various pollutants and harmful for drinking and recreational purposes. Most of the soil contains much higher values of heavy metals like Hg, Mn, Co and Zn than world wide average soil values (0.05, 270.00, 5.50, 45.00 ppm respectively). Therefore, it might have considerable negative effects on the soil quality, agricultural crops of the area and thus harmful for human health. Their higher concentration suggests that they resulted due to both natural origin and anthropogenic activities like, application of pesticides, mineral fertilization and industrial discharge. Keywords: Heavy metals; Physicochemical properties; Surface water soil quality; Human health. DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8117 Bangladesh J. Sci. Ind. Res. 46(1), 133-140, 2011